2012
DOI: 10.1007/s10689-012-9578-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study

Abstract: The primary aim of this study was to estimate the prevalence of BRCA1/2 mutations among familial breast cancer (BC) patients in Korea. We analyzed 775 familial BC patients who were enrolled in the Korean Hereditary Breast Cancer (KOHBRA) study and treated at 36 institutions between May 2007 and May 2010. Patients with familial BC were defined as BC patients with family histories of BC or ovarian cancer (OC) in any relatives. All probands received genetic counseling and BRCA genetic testing was performed after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 20 publications
10
37
1
3
Order By: Relevance
“…The prevalence of BRCA mutations was comparable to recently reported studies [19,20]. The relationships between genetic subtypes, MRI, and pathological findings were examined.…”
Section: Discussionsupporting
confidence: 73%
“…The prevalence of BRCA mutations was comparable to recently reported studies [19,20]. The relationships between genetic subtypes, MRI, and pathological findings were examined.…”
Section: Discussionsupporting
confidence: 73%
“…The prevalence of germline BRCA1/2 variants shows a large variation across different ethnicities, ranging from 6.5% to 25.0% in BC and from 12.1% to 29% in OC (Han et al, ; Kim et al, ; Robson et al, ; Weitzel et al, ). Due to remarkable advances in next‐generation sequencing (NGS) technologies (Rainville & Rana, ), it is now possible to investigate the prevalence of different BRCA1/2 variants in patients of distinct ethnicities, as well as their clinical significance (Sun et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 8.6-21.7 % of Korean patients with highrisk breast cancer have BRCA1/2 mutations [23,27,28]. Previous studies have shown that the frequency of BRCA1/ 2 mutations among Korean patients with familial breast cancer was lower than that in Western populations [23].…”
Section: Discussionmentioning
confidence: 99%